Porcine mononuclear phagocyte subpopulations in the lung, blood and bone marrow: dynamics during inflammation induced by Actinobacillus pleuropneumoniae - Ondrackova, Petra; Nechvatalova, Katerina; Kucerova, Zdenka; Leva, Lenka; Dominguez, Javier; Faldyna, Martin (Veterinary research, 2010)
Mononuclear phagocytes (MP) are cells of nonspecific immunity, playing an essential role in defense against bacterial pathogens. Although various MP subpopulations have been described in the pig, relations among these populations in vivo are unknown to date. The present study was aimed at describing porcine MP subpopulations infiltrating inflamed tissue of pigs under in vivo conditions. Actinobacillus pleuropneumoniae (APP) infection was used to induce an inflammatory response. CD172alpha, CD14, CD163, MHCII and CD203alpha cell surface molecules were used to identify MP by flow cytometry. Changes in MP subpopulations in the peripheral blood (PB) and bone marrow (BM) compartments along with the analysis of MP appearing in the inflamed lungs were assessed to elucidate the possible origin and maturation stages of the infiltrating MP. The MP population migrating to the inflamed lungs was phenotype CD14+ CD163+ CD203alpha+/- MHCII+/-. Concomitantly, after APP infection there was an increase in the PB MP CD14+ CD163+ CD203alpha- MHC II- population, suggesting that these cells give rise to inflammatory monocytes/macrophages. The CD203alpha and MHCII molecules appear on these cells after leaving the PB. In healthy animals, the BM MP precursors were represented by CD14- CD163- cells maturing directly into CD14+ CD163- that were then released into the PB. After infection, an altered maturation pathway of MP precursors appeared, represented by CD14- CD163- CD203alpha- MHCII- MP directly switching into CD14+ CD163+ CD203alpha- MHCII- MP. In conclusion, two different MP maturation pathways were suggested in pigs. The use of these pathways differs under inflammatory and noninflammatory conditions.
Keywords: Antigens, CD; fagocyty; CD antigeny; regulace genové exprese; Swine Diseases; Lung; zvířata; plíce; geny MHC třídy II; Swine; Phagocytes; Gene Expression Regulation; Actinobacillus pleuropneumoniae; nemoci prasat; Genes, MHC Class II; Bone Marrow Cells; infekce bakteriemi rodu Actinobacillus; Animals; Actinobacillus Infections; prasata; buňky kostní dřeně